Headache and Idiopathic Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Clinical characteristics of headache in 1,264 children with newly diagnosed idiopathic epilepsy were studied from 2006 to 2009 in five Italian Child Neurology University Centers.